Exenatide Treatment Causes Suppression of Serum Ghrelin Levels following Mixed Meal Test in Obese Diabetic Women - Figen Topyildiz; Sinem Kiyici; Zulfiye Gul; Deniz Sigirli; Metin Guclu; Gurcan Kisakol; Sinan Cavun (Journal of Diabetes Research)
Aim. To investigate the effect of exenatide treatment on serum ghrelin levels in obese female patients with type 2 diabetes mellitus. Methods. Fourteen female patients with type 2 diabetes mellitus being treated with metformin and exenatide were enrolled. A mixed meal test was applied to the patients while continuing with their daily medications. Blood samples were taken before and at 60, 120, and 180 minutes following mixed meal test to measure serum total ghrelin, glucose, and insulin levels. The following week, exenatide treatment of the patients was paused for 24 hours and the same experimental procedures were repeated. Results. Serum ghrelin levels were suppressed significantly at 180 minutes with exenatide treatment compared with baseline (294.4±57.5 versus 234.5±59.4 pg/mL) (p<0.001). Serum ghrelin levels at 180 minutes were statistically different when percentage change in serum ghrelin levels after mixed meal tests with and without exenatide usage were compared (p=0.001). Estimated total area under the curve values for serum ghrelin concentrations was also significantly lower with exenatide compared with omitted treatment (p=0.035). Conclusion. These results suggest that the effect of exenatide on weight loss may be related with the suppression of serum ghrelin levels, which is an orexigenic peptide.